THU0218 Circulating micrornas as biomarkers for diagnosis and typifying the atherothrombotic status in antiphospholipid syndrome. (15th June 2017) - Perez-Sanchez, C; Rosa, I Arias-de la; Aguirre, MA; Ruiz-Limon, P; Barbarroja, N; Jimenez-Gomez, Y; Abalos-aguilera, MC; Collantes-Estevez, E; Teresa-Herranz, M; Lozano-Herrero, J; Martinez, C; Gonzalez-Conejero, R; et al.
Abstract : Background: The course of antiphospholipid syndrome (APS) may rapidly progress from asymptomatic to severe manifestations. Thus, timely diagnosis is essential to improve accuracy of therapy. The role of circulating microRNAs (miRNAs) as potential biomarkers of disease has not yet been analysed in APS. Objectives: To investigate the contribution of circulating miRNAs to the pathogenesis of APS and their potential role as non-invasive biomarkers of the disease. Methods: Ninety APS patients and 42 healthy donors (HD) were included in the study. Clinical and inflammatory parameters were analysed. As a complement to standard clinical follow-up, the ankle-brachial index (ABI) and carotid intima-media thickness (CIMT) were determined. miRNA expression profiling was performed in plasma by PCR-Array, and the Ingenuity Pathways analysis software (IPA) was used to identify specific miRNAs and target proteins associated to the pathogenesis of APS. RT-PCR and ELISA/Bioplex of selected genes and proteins were used to validate microarray data. The diagnostic value of specific miRNAs signatures (ratios) as disease biomarkers was evaluated by ROC curves analysis. To assess the specificity of these signatures in APS, the expression of the selected miRNAs was analysed in plasma from 23 thrombotic patients without associated autoimmune disease. Monocytes isolated from HD and endothelial cells (ECs) were treated in vitro with antiphospholipid antibodies (aPL-IgGs) purified from the serum of APS patients, and the changes promoted on the levels of selected miRNAs and their potential targets were analysed. Results: The PCR-Array identified 39 circulating miRNAs differentially expressed, including 19 up-regulated and 20 down-regulated in APS. IPA analysis recognized 11 miRNAs as potential modulators of target genes involved in the physiopathology of APS. Logistic Regression and ROC curve analyses identified a signature of 10 miRNA ratios as biomarkers for diagnosis of APS with great accuracy (AUC:0.81), along with 2 miRNA ratios as biomarkers for typifying the atherothrombotic status (pathologic CIMT) of APS (AUC:0.76). Patients with thrombosis but without associated autoimmune disease displayed a specific miRNA profile, distinct from that of APS patients. The miRNA signature was related to clinical features of APS such as the occurrence of foetal loss and the type of thrombosis suffered, and correlated with parameters linked to autoimmunity (aPL-IgG titers), inflammation, and thrombosis (ABI, ESR, TF, PAI-1, MCP-1, VEGF-A and VEGF-R1). In vitro treatment of monocytes and endothelial cells with aPL-IgG antibodies promoted a significant deregulation in the secreted levels of the selected miRNAs and atherothrombotic target proteins. Conclusions: miRNA levels in the serum of APS patients -modulated by aPL-IgG antibodies- are potential novel biomarkers for diagnosis and typifying of their atherothrombotic status, thus constituting a useful tool in the prevention and management of the disease. Acknowledgements: Supported by CTS794 and ISCIII (FIS15/1333 and RIER RD16/0012/0015). Disclosure of Interest: None declared